Fast progression in non–small cell lung cancer: results from the randomized phase III OAK study evaluating second-line atezolizumab versus docetaxel. Issue 3 (18th March 2021) - Gandara, David; Reck, Martin; Moro-Sibilot, Denis; Mazieres, Julien; Gadgeel, Shirish; Morris, Stefanie; Cardona, Andres; Mendus, Diana; Ballinger, Marcus; Rittmeyer, Achim; Peters, Solange
Abstract : Background: Treatment-induced accelerated tumor growth is a progression pattern reported with immune checkpoint inhibitors that has never been evaluated in randomized phase III studies because it requires two pretreatment scans. This study aimed to develop clinically relevant and applicable criteria for fast progression (FP), incorporating tumor growth kinetics and early death from disease progression to analyze data from the randomized phase III OAK study. Methods: The OAK study evaluated the efficacy and safety of atezolizumab versus docetaxel as second-line or third-line treatment for stage IIIb/IV non–small cell lung cancer. FP rates and associated baseline factors were analyzed. FP was defined as either a ≥50% increase in the sum of largest diameters (SLDs) within 6 weeks of treatment initiation or death due to cancer progression within 12 weeks (absent post-baseline scan). Results: Forty-two of 421 patients (10%) receiving atezolizumab and 37 of 402 (9%) receiving docetaxel had FP. Twenty patients with FP (48%) receiving atezolizumab versus 12 (30%) receiving docetaxel had a ≥50% SLD increase within 6 weeks. FP was significantly associated with an ECOG (Eastern Cooperative Oncology Group) performance status of 1 (vs 0), ≥3 metastatic sites at baseline, and failure of preceding first-line treatment within 6 months, but not with epidermal growth factor receptor mutation, programmed cell death 1 ligand 1 or tumor mutational burden. Overall survival in patients with FP and a ≥50% SLD increase at week 6 was similar with atezolizumab and docetaxel (unstratified HR 0.89 (95% CI 0.41 to 1.92)). Conclusions: FP rates were similar with atezolizumab and docetaxel in the OAK study, suggesting that FP may not be unique to checkpoint inhibitors, although the underlying mechanisms may differ from those of chemotherapy. Applying the FP criteria to other phase III checkpoint inhibitor trials may further elucidate the risk factors for FP. Trial registration number: NCT02008227 .